2011
DOI: 10.1111/j.1573-7861.2011.01238.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk as Social Context: Immigration Policy and Autism in California1

Abstract: Motivated by the dramatic increase in autism diagnoses in recent years, research into risk factors has uncovered substantial variation in autism prevalence by race/ethnicity, SES, and geography. Less studied is the connection between autism diagnosis rates and the social and political context. In this article, we link the temporal pattern of autism diagnosis for Hispanic children in California to state and federal anti-immigrant policy, particularly ballot initiative Proposition 187, limiting access to public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 38 publications
2
34
0
2
Order By: Relevance
“…Recently, scholars have begun to examine the effect of racialized 2 political events and decisions on minority health (Fountain and Bearman 2011;Lauderdale 2006;Malat, Timberlake, and Williams 2011;Moller 1998). They argue that political events with racial=eth-ethnic implications can affect the health of those groups targeted by the events, either positively or negatively (Fountain and Bearman 2011;Lauderdale 2006;Malat et al 2011;Moller 1998).…”
mentioning
confidence: 98%
“…Recently, scholars have begun to examine the effect of racialized 2 political events and decisions on minority health (Fountain and Bearman 2011;Lauderdale 2006;Malat, Timberlake, and Williams 2011;Moller 1998). They argue that political events with racial=eth-ethnic implications can affect the health of those groups targeted by the events, either positively or negatively (Fountain and Bearman 2011;Lauderdale 2006;Malat et al 2011;Moller 1998).…”
mentioning
confidence: 98%
“…Maternal immigrant status is another social factor that emerged in eight studies 104,208,243,[247][248][249][250][251] and two systematic reviews 13,100 supporting an association with ASD or ASD subtype. Migrant mothers had a higher prevalence of offspring with ASD in studies from Sweden, the United Kingdom and Australia.…”
Section: Immigrant Statusmentioning
confidence: 99%
“…15,16 Given the growing number of children from immigrant families, the differences in prevalence of ASDs and select DDs across studies, [17][18][19] and the complexity of service systems for ASDs and DDs, it is important to understand the patterns of health care experience for families and maximize health outcomes of children with ASDs and select DDs from immigrant families to minimize overall cost for all stakeholders. 20,21 Select DDs in this study includes children reported having ADHD or attention deficit disorder (ADD), learning disabilities, and any developmental delay, which are highly prevalent DDs. 22 Our study is the first to explore this important public health issue by examining the relationship between immigrant household status and access to a medical home, insurance, and education services for children with ASDs and select DDs by using the data from the 2007 National Survey of Children' s Health (NSCH) and the 2007 NSCH medical home composite measure.…”
mentioning
confidence: 99%